The role of water in the formation of crystal structures: a case study of valnemulin hydrochloride. Issue 1 (15th December 2020) - Li, Shuyu; Wang, Ting; Huang, Xin; Zhou, Lina; Chen, Mingyu; Liu, Wanying; Zhang, Xiunan; Dong, Yuyuan; Hao, Hongxun
Abstract : Water molecules play a key role in the formation of crystalline state valnemulin hydrochloride. Abstract : In this work, a crystalline dihydrate form of valnemulin hydrochloride (VHW) was discovered and characterized. The single crystal data of VHW were determined and analyzed. Compared with the two valnemulin hydrochloride solvates reported previously, VHW exhibits better stability. From the crystal structure analysis of the three crystal forms and molecular conformation analysis, it was found that water molecules play a key role in the formation of crystalline state valnemulin hydrochloride. At the same time, it was found that except for packing, conformational similarity also has a certain effect on the polymorphic transformation behaviors of different forms of valnemulin hydrochloride.